Significado da formação e inserção profissional para gerentes e aprendizes egressos do Programa Jovem Aprendiz - Máximo, Thaís Augusta Cunha de Oliveira (2012)
The objective of this thesis was to analyze the meaning of training and integration into the job market for graduate apprentices and managers of the Apprenticeship Program. To capture the meaning and the sense, Vigotski s Cultural-historical Psychology. The research was performed starting from three studies. The first study was a systematic literature review on youth and public policies taken from the literature published in Scielo portal in the last 10 years (2001-2011). The second study was a documentary research carried out at all the training institutions in the city of João Pessoa and the Regional Department of Labor and Employment (SRTE / PB), with the purpose of mapping the Program, as well as gathering all necessary information to carry out the third study. The last study consisted of 20 semi-structured interviews―10 with graduate apprentices and 10 with managers. For the literature review, a form was used which categorized information such as year of publication, distribution area of the magazine, main subject, type of article (theoretical review or research report), viewpoint used, if the study was qualitative, quantitative or quali-quantitative. For the documentary research, a descriptive analysis of the protocols, reports and study programs obtained from the institutions was performed. For the analysis of the interviews, the Lexical Analysis of the ALCESTE software was utilized. The results of the first study showed that the main issues that emerged regarding youth were sexuality, violence, risks, and vulnerability. The psychology articles represented 15.20% of the publications; however, despite having achieved the third place in comparison with other areas, the first publication in a specialized magazine was in 2004. The data from the second study pointed out that most apprentices achieve integration through supervisory action, which means that the companies only accept young people under the demands of the supervisory organization. In regard to the third study, the speech also denotes the meaning of work as an antidote against the risks of youth. In regard to the expectation of the young people in terms of their participation in the program, the speech shows the importance of integration into the job market, stated as a salvation for those young people. Regarding the functions of the apprentices in the companies, the study identified that they are driven around and placed at the mercy of the company's needs. Regarding post-program market integration, those who were hired ended up working in activities that were temporary, outsourced, and mostly unrelated to the course taken during the apprenticeship. Data analysis of the managers showed that most companies have joined the program only as result of fiscal supervision, and that they are critical of the courses in terms of cost, superficiality of the material taught, and the lack of a more systematic collaboration between the companies and the training institutions. The execution of other studies has been suggested in order to further investigate the aspects related to work overload, conciliation between work and school, lack of fiscal supervision regarding the young people s activities in the companies, as well as the content of the courses offered by the training institutions.